Analysis and Interpretation of Airborne Magneticdata of G.Abu Had-G.Umm Qaraf Area, South Eastern Desert, Egypt (Global Journal of Science Frontier Research, 2016)
The aeromagnetic survey is important to delineate the relationship that is usually present in survey areas, between magnetic anomalies and tectonic pattern. This is primarily based on the fact that the tectonic history of the rocks is recorded in the magnitude and pattern of magnetic anomalies. Thus, any extensive magnetic survey will contain anomalies whose pattern is not random. G.Abu Had-G.Umm Qaraf area is located in the southern part of the Eastern Desert of Egypt. It is about 100 km southwest Marsa Alam City. This approach utilized interpretation techniques that independent of magnetization direction such as source parameter imaging, Euler deconvolution and analytic signal to estimate body location and depth. The estimated parameters were further used to image the basement rocks using modeling techniques.
Keywords: delineate; aeromagnetic survey; magnetic anomalies